EFFECT OF OSMOTIC DEHYDRATION IN THE APPLE (Pyrus malus) VARIETIES GALA, GOLD AND FUJI - Moura, C. P.; Masson, M. L.; Yamamoto, C. I. (Revista de Engenharia Térmica, 2005)
Some raw material characteristics were evaluated in three apple varieties Gala, Gold and Fuji. The study was undertaken to collect information in order to identify the effects of initial tissue properties on mass transport phenomena in general, and osmotic processing responses in particular. The apples, obtained from the local market, were washed, peeled and cut into 10 mm cube. After this, the samples were dehydrated in sugar osmotic solution (50% w/w) at 30°C and 110 rpm of agitation. The ratio of foodstuff to osmotic solution was greater than 1:20. The mass transfer kinetics was measured in intervals of 20 minutes during 3 hours. The mass transfer kinetics of the different apple varieties has presented different behavior during the osmotic dehydration. The apples vs. Gala have presented the highest water loss and solid gain. The vs. Gold presented a lower tendency to solid uptake.